A Study on Investment Performance of Private Sector Banks Mutual Fund Schemes (With Special Reference to Equity Linked Saving Schemes (ELSS) - K. Venkata Rami Reddy , Prof. A. Sreeram (International Journal of Modern Agriculture, 2020)
Mutual funds allow diversification of portfolios and relative risk aversion. Equity linked saving schemes (ELSS) in India is a form of mutual fund scheme that allows investments in equity securities issued by companies, banks and government etc. Provides Income tax benefits on the investment (up to a maximum of Rs. 1.50 lack per financial year under Sec 80C of the Income Act, 1961) and is creating wealth over the long period. Top five private sector banks (in terms of Assets under management (AUM) volume) are considered to evaluate performance for a period of 5 years from 1st April 2014 to 31st march 2019. Performance has been evaluated by comparing annual average returns with average returns of Index Nifty 50 TRI. Various tools like average return, Standard Deviation (SD), Coefficient of Variance (CV), beta, Sharpe ratio, Treynors ratio and Jensen alpha has been used for the study. The study concludes that all selected ELSS (Direct-Growth) have outperformed the market index in terms of average return and are more risky.